2000
DOI: 10.1177/0273475300223006
|View full text |Cite
|
Sign up to set email alerts
|

Marketing and the Creative Problem-Solving Process

Abstract: In the aggregate, marketing may be conceptualized as the process of offering creative solutions to consumer problems. As such, educational emphasis should be given to increasing students’ knowledge of the creative problem-solving (CPS) process. Unfortunately, past research has given little attention to the CPS process itself. The purpose of this article is to better familiarize marketing educators with the CPS process and its connection to marketing practice. In addition, an instructional approach is offered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 11 publications
1
76
0
Order By: Relevance
“…As stated earlier, researchers have repeatedly viewed creativity as an activity designed to solve challenging problems in a novel manner… Amabile (1983) suggested that creative ideas or solutions should be useful, novel, and appropriate to the task at hand. The theoretical perspective of creativity adopted here is consistent with past marketing research that has viewed creativity as a problem-solving activity (Anderson, 2006;Lunsford, 1990;Titus, 2000) (Excerpt from Titus, 2007).…”
Section: Introductionsupporting
confidence: 65%
“…As stated earlier, researchers have repeatedly viewed creativity as an activity designed to solve challenging problems in a novel manner… Amabile (1983) suggested that creative ideas or solutions should be useful, novel, and appropriate to the task at hand. The theoretical perspective of creativity adopted here is consistent with past marketing research that has viewed creativity as a problem-solving activity (Anderson, 2006;Lunsford, 1990;Titus, 2000) (Excerpt from Titus, 2007).…”
Section: Introductionsupporting
confidence: 65%
“…Using an example of Matsushita Electric Industrial Company, Gross (1989) suggests that innovation can be achieved by focusing on a series of small, incremental changes of product/service. Not only does marketing try to solve customers' problems in creative ways, but it also can be viewed as the process of developing and offering creative or innovative solutions to customer problems (Titus, 2000). In other words, the process of coming up with an innovation product/service may be as important as the innovative finished product/service.…”
Section: Innovationmentioning
confidence: 99%
“…Possible ways of improving equipment has been tied to sensitivity to problems, just to name one industrial example (Merrifield et al, 1962). Titus (2000) argued that:…”
Section: Evaluation Of Ideasmentioning
confidence: 99%